BISALBUMINEMIA: STILL UNREVEALED FOR CLINICIANS AND RESEARCHERS – A SYSTEMIC REVIEW - SNEHA WADALKAR; SHALINI MAKSANE; KAVITA MORE; KSHAMA PIMPALGOANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Bisalbuminemia, a rare finding on serum protein electrophoresis, presents as a double band in the albumin region. Inherited Bisalbuminemia is a benign condition with autosomal dominant inheritance whereas Acquired Bisalbuminemia can be associated with various conditions like diabetes, pancreatitis, and myeloma. Capillary electrophoresis is the preferred method for diagnosis due to its superior resolution compared to agarose gel electrophoresis. Bisalbuminemia itself has no clinical significance, but acquired forms warrant further investigation for underlying diseases. Future research focuses on the functional consequences of albumin mutations and potential disease associations. This review summarizes the current knowledge on Bisalbuminemia, covering its types, causes, clinical significance, and diagnosis.